Effect of toning pants on energy cost and muscle activation - Kleingartner, Alexa J. (My University, 2012)
The purpose of this study was to determine the effects of wearing Fila toning capris on energy cost, heart rate, rating of perceived exertion (RPE), and muscle activation. Sixteen females, ages 18-24 years, were asked to perform two randomized treadmill trials. During one trial, subjects wore regular athletic shorts, while during the next trial su~jects wore Fila toning capris. During each of the trials subjects walked a total of 15 minutes (five minutes at 2.5, 3.0, 3.5 mph on a level treadmill). During each trial, oxygen consumption (V02), heart rate, RPE, and electromyography (EMG) were recorded. EMG was used to measure the muscle activation of the subjects' gluteus maximus, bicep femoris, and vastus lateralis. Results showed a significant difference in vo2 (15.3 vs 14.9 mllkg/min) and RPE (9.2 VS 8.8) when wearing the Fila toning capris versus athletic shorts. However, there were no significant differences found in muscle activation between the Fila toning capris and athletic shorts
Keywords: Exercise -- Physiological aspects